Insight into the microplastics release from disposable face mask: Simulated environment and removal strategy. (December 2022) - Jiang, Hongru; Su, Jiming; Zhang, Yingshuang; Bian, Kai; Wang, Zhiyi; Wang, Hui; Wang, Chongqing
Abstract: The fight against the COVID-19 epidemic significantly raises the global demand for personal protective equipment, especially disposable face masks (DFMs). The discarded DFMs may become a potential source of microplastics (MPs), which has attracted much attention. In this work, we identified the detailed source of MPs released from DFMs with laser direct infrared spectroscopy. Polypropylene (PP) and polyurethane (PU) accounted for 24.5% and 57.1% of released MPs, respectively. The melt-blown fabric was a dominant MPs source, however, previous studies underestimated the contribution of mask rope. The captured polyethylene terephthalate (PET), polyamide (PA), polyethylene (PE), and polystyrene (PS) in airborne only shared 18.4% of released MPs. To deepen the understanding of MPs release from medical mask into the aquatic environment, we investigated the effects of environmental factors on MPs release. Based on regression analysis, the effects of temperature, incubation time, and wearing time significantly affect the release of MPs. Besides, acidity, alkalinity, sodium chloride, and humic acid also contributed to the MPs release through corroding, swelling, or repulsion of fibers. Based on the exposure of medical mask to simulated environments, the number of released MPs followed the order: seawater > simulated gut-fluid > freshwater > pure water. Considering the risk of MPs released from DFMs to the environment, we innovatively established a novel flotation removal system combined with cocoamidopropyl betaine, achieving 86% removal efficiency of MPs in water. This work shed the light on the MPs release from DFMs and proposed a removal strategy for the control of MPs pollution. Graphical abstract: Image 1 Highlights: Mask rope was identified as a dominant source of microplastics. Temperature, wearing time, and incubation time promoted microplastics release. The release of microplastics was affected by pH, sodium chloride, and humic acid. Disposable face mask released more microplastics in seawater and gut-fluid. Froth flotation with cocoamidopropyl betaine removed microplastics efficiently.